Mediating Effect of Trust and Commitment on Student Loyalty - Herry Mulyono (Business and Entrepreneurial Review, 2014)
In facing the competitive market structure, Private University is forced to compete in order to attract students and to preserve them until graduation, continue their study to the higher leveland to distribute positive information by word of mouth amongst the community as a form of persuasion to others. The purpose of this research is to analyze : The effect of image, perceivedquality, and perceived value on student satisfaction, The effect of Student Satisfaction on Student loyalty mediated by trust and commitment. The source of the data is secondary data taken from The Ministry of National Education (Kemdiknas), Kopertis region III and the primary data is taken from a survey of Private University students in Jakarta, with the number of samples being= 500, analyzed by using Structural Equation Modeling (SEM) Lisrel 8.80.The findings of this research are: six hypothesis take positive effect and significant. Student loyalty is not influenced by student satisfaction mediated by trust (No mediating), Student loyalty is influenced by student satisfaction mediated by commitment (full mediating).